(untitled) (International Journal of Environmental Sciences, 2024)
The present study investigates "the impact of social media on the personal values ​​of students in Higher Secondary Schools of Raipur District." For this research, schools at the higher secondary level were selected using the random sampling method. A sample comprising 100 students (50 boys and 50 girls) was selected. For data collection, the researcher utilized two standardized instruments: the ’Social Media Scale,’ developed by Balwinder Singh and Surjit Lal, and the ’Personal Values ​​Scale,’ developed by Archana Dubey and Mahendra Patidar. The survey method was employed for this research study. The research findings revealed that a significant difference was observed regarding the impact of social media on the personal values ​​of male students in higher secondary schools. Similarly, a significant difference was found regarding the impact of social media on the personal values ​​of female students in higher secondary schools. Overall, a significant difference was observed regarding the impact of social media on the personal values ​​of students in higher secondary schools.